"Comparative Evaluation of the Initial Corrosion of four Brands of High Copper Dental Amalgams " - MH. Fathi; V. Mortazavi (Tehran University of Medical Sciences, 2004)
Statement of Problem: Many attempts have been made in order to evaluate the amalgam corrosion behavior as an indicator of biocompatibility. Purpose: The aim of this study was to evaluate and compare the initial corrosion of four different brands of dental amalgams. Materials and Methods: Four different types of commercial high copper dental amalgam were studied. A special mold was used and twenty-one samples of each type of commercial dental amalgams were prepared. X-ray diffraction technique was used to investigate the microstructure of freshly prepared specimens. Electrochemical potentiodynamic tests were performed in physiological solutions in order to determine and compare the corrosion behavior of freshly prepared sample of four brands of dental amalgams. The physiological solutions were the Ringer's solution and physiological normal saline. Five replicate tests on each group of specimens were performed. Tafel extrapolation and linear polarization methods determined corrosion potentials and corrosion current densities. The mean value and standard deviations of the results were calculated. The mean values were statistically compared by ANOVA and Duncan methods at 95% level of confidence. Results: Gamma-2 phase was present in freshly prepared sample of each type of commercial amalgam. The results showed statistically significant differences between the mean corrosion current density values of freshly prepared sample of four brands of amalgams (P